2003
DOI: 10.1177/000841740307000106
|View full text |Cite
|
Sign up to set email alerts
|

Private Practice: Benefits, Barriers and Strategies of Providing Fieldwork Placements

Abstract: The findings have implications for increasing private practice placements for future students in occupational therapy and other health care professions offering clinical placements as a component of their formal education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 16 publications
3
27
0
5
Order By: Relevance
“…The location of this survey in Queensland, Australia, may not be generalisable to other Australian states and territories, nor to international settings. However, the similarity of some of its findings when compared with recent literature from Canada (Sloggett, 2003) is encouraging. The survey design, and its distribution via email, resulted in an estimated response rate of 42%; however, it is not known how many potential participants the email finally reached.…”
Section: Study Limitationssupporting
confidence: 60%
See 1 more Smart Citation
“…The location of this survey in Queensland, Australia, may not be generalisable to other Australian states and territories, nor to international settings. However, the similarity of some of its findings when compared with recent literature from Canada (Sloggett, 2003) is encouraging. The survey design, and its distribution via email, resulted in an estimated response rate of 42%; however, it is not known how many potential participants the email finally reached.…”
Section: Study Limitationssupporting
confidence: 60%
“…While Canadian researchers (e.g. Sloggett, Kim & Cameron, 2003;Tompson & Proctor, 1990) have conducted several investigations into this topic, these studies have generally been relatively small in scope and, given differences in health and education systems, may not fully reflect the contemporary experiences and perceptions of Australian fieldwork supervisors.…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative approach was used by Sloggett et al (2003) to discover benefits and barriers of providing fieldwork placements in the specific venue of private practice in Canada. Results revealed that the benefits of providing fieldwork in private practice affect the profession, individual practitioners, and the clients served.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the profession of occupational therapy, a limited number of contemporary research studies have been conducted to specifically explore occupational therapists' perceptions of benefits, barriers, and facilities for supervising students (Brayford et al, 2002;Casares, Bradley, Jaffe, & Lee, 2003;Derdall & Urbanowski, 1995;Sloggett, Kim, & Cameron, 2003;Thomas et al, 2007;Vogel, Grice, Hill, & Moody, 2004).…”
mentioning
confidence: 99%
“…Au Québec, cette proportion s'élève à 31% selon le rapport annuel 2015-2016 de l'Ordre des ergothérapeutes du Québec (OEQ) [2]. Ce secteur de la pratique ergothérapique est en croissance constante, au Canada [1] et au Québec [3] comme à l'échelle internationale [4]. Comme les ergothérapeutes qui travaillent dans le secteur public, ceux du secteur privé interviennent en santé mentale et physique auprès d'enfants, d'adultes ou de personnes âgées.…”
Section: Introductionunclassified